Marcha Nico Lopes - S/A (Arquivo Central e Histórico da UFV, 2019)
Alunos fantasiados na Nico Lopes caminhando para a Cidade.
Keywords: Marcha Nico Lopes; Alunos; Fantasias; Memória UFV::Acervo Fotográfico::ESAV::Eventos, Eventos Culturais e Projetos::Marcha Nico Lopes